Memories, Identity, and Indigenous/National Subjectivity in Eastern Peru - Veber, Hanne (Diálogos Latinoamericanos, 2007)
In Latin America the forging of national identities has been problematic, especially in countries where large indigenous populations have remained marginalized through colonial ideologies of exclusion. This is changing, however, as processes of globalization are reshuffling old orders and indigenous people become active participants in new social movements of their own making. Founded on shared experience and emergent feelings of solidarity, a new political body is created, defined by indigeneity and shared interests vis-à-vis the state. Based on autobiographical narratives from Asháninka leaders in the central Amazon of Peru, the paper looks at the memory-identity nexus and the way it is reflexively tied to the process of forging new political subjectivity as Asháninka and Peruvian citizens. Even if indissolubly linked with a verifiable past, Asháninka memories are also the products of signifying processes associated with the present, with hopes and dreams, and with the production of meaning in the context of decolonization.